Examining the level of motivation of foreign students during studying in Kazakhstan - Джугал, Панчал; Оспанова, Мадина (Pedagogy and Psychology, 2020)
The article deals with the problem of motivation in the student sphere. If we talk about the motivation of students, it represents the processes, methods and means of inducing them to cognitive activity, active development of the content of education. As motives can act in conjunction emotions and aspirations, interests and needs, ideals and attitudes. Therefore, motives are complex dynamic systems in which choice and decision-making, analysis and evaluation of choice are carried out. Motivation for students is the most effective way to improve the learning process. Motives are the driving forces of the learning process and assimilation of the material. Motivation for learning is a rather complicated and ambiguous process of changing the attitude of the individual, both to a separate subject of study and to the entire educational process. Motivation is the main driving force in human behavior and activity, including in the process of forming a future professional. Therefore, the question of incentives and motives of educational and professional activity of students becomes especially important.